12y-1=16y

Combine 12 and y.

y2-1=16y

Combine 16 and y.

y2-1=y6

Subtract y6 from both sides of the equation.

y2-1-y6=0

To write y2 as a fraction with a common denominator, multiply by 33.

y2⋅33-y6-1=0

Write each expression with a common denominator of 6, by multiplying each by an appropriate factor of 1.

Multiply y2 and 33.

y⋅32⋅3-y6-1=0

Multiply 2 by 3.

y⋅36-y6-1=0

y⋅36-y6-1=0

Combine the numerators over the common denominator.

y⋅3-y6-1=0

Subtract y from y⋅3.

Reorder y and 3.

3⋅y-y6-1=0

Subtract y from 3⋅y.

2⋅y6-1=0

2⋅y6-1=0

Cancel the common factor of 2 and 6.

Factor 2 out of 2⋅y.

2(y)6-1=0

Cancel the common factors.

Factor 2 out of 6.

2y2⋅3-1=0

Cancel the common factor.

2y2⋅3-1=0

Rewrite the expression.

y3-1=0

y3-1=0

y3-1=0

y3-1=0

Add 1 to both sides of the equation.

y3=1

Multiply both sides of the equation by 3.

3⋅y3=3⋅1

Cancel the common factor of 3.

Cancel the common factor.

3⋅y3=3⋅1

Rewrite the expression.

y=3⋅1

y=3⋅1

Multiply 3 by 1.

y=3

y=3

Solve for y 1/2y-1=1/6y